Gougerot-Carteaud syndrome treated with acitretin: A case report - Demir, Betul; Agar, Sultan; Karstarli, Ozge Sevil; Cicek, Demet; Ucer, Ozlem (Deri Zuhrevi Hastaliklar Dernegi, 2017)
Gougerot-Carteaud syndrome (GCS) is a rarely seen dermatosis characterized by reticular and pigmented plaques with a tendency to merge with each other in areas such as the neck, upper body, and axilla in young adults. A 20-year-old male patient presented to the dermatology outpatient clinic with the complaints of itching and brown patches affecting the trunk, back and the neck. He had no endocrine diseases and used no drugs. Dermatological examination revealed reticulated, hyperpigmented, verrucous papules and plaques on the anterior surface of his trunk, upper back, and neck region. No fungal elements were encountered in the potassium hydroxide examination. Histopathologically, basket-like hyperkeratosis, papillomatosis, mild acanthosis, and hyperpigmentation in the basal layer were detected. Minocycline treatment was initiated at a dose of 100 mg/daily. At the three-month follow-up visit, minocycline treatment was terminated due to lack of clinical response, and 30 mg/day acitretin treatment was initiated. The lesions showed marked improvement except for a slight hyperpigmentation in the first month of the treatment. We report here a case of GCS in which acitretin was started due to clinical unresponsiveness to minocycline treatment and, substantially, a favorable result was obtained in a short time.
Keywords: Gougerot-Carteaud syndrome; confluent and reticulated papillomatosis; acitretin